Efficacy of some local isolates of the fungus Beauveria bassiana (Balsamo) against the immature stages of the European corn borer, Ostrinia nubilalis (Hübner( in the laboratory (Damascus University Journal of agriculture sciences, 2024)
The research was carried within Biological Control Studies and Research Center (BCSRC), in the Faculty of Agricultural Engineering at University of Damascus during years 2020-2022. The pathogenicity of 7 isolates of Beauveria bassiana was evaluated on the immature stages of Ostrinia nubilalis. Isolates BS.5 and KA.1 caused the highest newly hatched larvae mortality of 56.53 and 51.10%, respectively, when applied. At aconcentration of 1 x 108 spores/ml after 7 days of treatment, the rate of its effect on second instar larvae decreased, as isolate KA.1 caused the highest death rate of 28.33% at the same concentration and there was no significant effect on second instar larvae and pupae, where the highest death rate was in the pupae of isolate KA.1 reached 23.21% after two weeks of treatment. Therefore, it can be said that it is possible in the future to develop a test using the fungus B. bassiana in the field with high efficiency in controlling the European corn borer community, especially in the early stages of its life.
Keywords: Entomopathogens; Fungi; Immature Stages; Ostrinia Nubilalis